2019
DOI: 10.1021/acs.joc.9b01900
|View full text |Cite
|
Sign up to set email alerts
|

Lewis Acid-Mediated Cyclization of Allenyl Aryl Ketones

Abstract: The cyclization of a series of nonheterocyclic allenyl aryl ketones was examined using boron trifluoride etherate and indium triflate to mediate the reaction. Yields with BF3 were low in most instances due mainly to competitive destruction of the substrates. With In­(OTf)3, there was less decomposition, and the yields of the cyclized product were much higher, but only for substrates with electron-donating substituents. Cyclization did not occur without those substituents. A computational study using the ωB97X-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…It has been found that electron‐donating substituents notably increased the yield of the transformation. Also, DFT calculations have pointed to a more plausible 4π‐electrocyclization mechanism versus a 5‐ endo ‐ dig ring closing reaction (Scheme 43a) [138] . In a similar report, cationic iron catalysts have been employed to perform the cyclization of related AAKs 228 b (Scheme 45b) [139] .…”
Section: Synthetic Utilitymentioning
confidence: 98%
See 3 more Smart Citations
“…It has been found that electron‐donating substituents notably increased the yield of the transformation. Also, DFT calculations have pointed to a more plausible 4π‐electrocyclization mechanism versus a 5‐ endo ‐ dig ring closing reaction (Scheme 43a) [138] . In a similar report, cationic iron catalysts have been employed to perform the cyclization of related AAKs 228 b (Scheme 45b) [139] .…”
Section: Synthetic Utilitymentioning
confidence: 98%
“…In recent years, different reports have described the synthesis of those systems within more complex structures. [128][129][130][131][132][133][134][135][136][137][138][139][140][141] Also, tandem processes have been described involving Lewis acid-promoted Nazarov cyclizations towards the synthesis of cyclopentenones exhibiting diverse functionalization. Thus, AVK molecules have been recurrently employed in the so-called "interrupted Nazarov cyclization", where the Nazarov carbocation intermediate 215 is trapped with different nucleophiles at either position C2' or C4 generating highly substituted cyclopentenones.…”
Section: Synthesis Of Cyclopentenonesmentioning
confidence: 99%
See 2 more Smart Citations
“…OEt 2 ) or indium triflate to afford indanone derivatives 46 along with the formation of indenone as minor product 47 (Scheme 15). [42] Yields with BF 3 were low in most of the cases due to mainly competitive destruction of the substrates. With indium triflate, there was less decomposition of product but only for the substrates containing electron donating groups.…”
Section: Acid‐catalyzed Synthesismentioning
confidence: 99%